Modele ekonometryczne handlu zagranicznego (na przykładzie lat 1991-2002 w Polsce) - Broszkiewicz, Ryszard (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The main objective of the article is the presentation of econometric models concerning Polish foreign trade. The period of statistical observation is set on years 1991-2002, when the restructurization processes took place and the private sector and market economy have been established. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 53-62